Remote Work, Wages, and Hours Worked in the United States - Sabrina Wulff Pabilonia; Victoria Vernon (Global Labor Organization (GLO), 2023)
Remote wage employment gradually increased in the United States during the four decades prior to the pandemic, then surged in 2020 due to social distancing policies implemented to stem the spread of COVID-19. Using the 2010-2021 American Community Survey, the authors examine trends in wage and hours differentials for full-time remote workers and office-based workers as well as within occupation differences in wage growth by work location. Throughout the period, remote workers earned higher wages than those working on-site, and the difference increased sharply during the pandemic. Real wages grew 4.4 percent faster for remote workers within detailed occupation groups and remote work intensity was positively associated with wage growth across occupations. Before the pandemic, remote workers worked substantially longer hours per week than on-site workers, but by 2021, hours were similar.
Keywords: J20; J22; J31; 330; remote work; working from home; wages; usual hours worked; COVID-19